College accounting - McQuaig, Douglas J. (Houghton Mifflin, 2008)
The Ninth Edition of College Accounting retains the successful characteristics that make it a market leader--accuracy, careful pacing, and repetition of accounting terms, concepts, and procedures--while integrating Internet features that provide students with real-world business experience